The metabolism of abscisic acid in higher plant tissues - Cowan, Ashton Keith (Rhodes University, Faculty of Science, Botany Department, 1989)
The biosynthesis of ABA from R-[2-Â¹â ´C]-MVA was demonstrated in Persea americana cv. Fuerte mesocarp and in mature seeds of Hordeum vulgare cv. Dyan and cv. Himalaya. Radioactivity from R-[2-Â¹â ´-C]-MVA was also incorporated into the 1',4'-trans ABA diol in Persea americana mesocarp and a possible role for this metabolite as a precursor of ABA in plants is discussed. The biosynthesis of ABA from MVA could not be demonstrated in either turgid and waterstressed Hordeum vulgare cv. Dyan, Pisum sativum cv. Black-eyed Susan and Phaseolus vulgaris cv. Top-crop or in immature seeds of Pisum sativum and Phaseolus vulgaris. (R,S,)-[2-Â¹â ´C]-ABA was catabolised to PA, DPA and aqueous conjugates in leaves and mature seeds of Hordeum vulgare cv. Dyan, seedlings and immature seeds of Pisum sativum and Phaseolus vulgaris and in mesocarp from ripening fruits of Persea americana. PA and DPA were identified by either microchemical methods and/or capillary GC-MS. 7'-Hydroxy ABA was characterised as a novel ABA catabolite in light-grown and etiolated leaves of Hordeum vulgare by capillary GC-MS. Circular dichroism analysis revealed that it was derived predominantly from the (R)-enantiomer of ABA. This catabolite was absent in similar studies using the dicotyledons Pisum sativum and Phaseolus vulgaris. Refeeding studies with [Â¹â ´C]-PA, [C]-DPA and [Â¹â ´C]-7'-hydroxy ABA were used to confirm the metabolic interrelationship between ABA and its catabolites in both vegetative and non-vegetative tissues from monocotyledonous and dicotyledonous species. The methyl ester of (R,S,)-ABA was hydrolysed efficiently by light-grown leaves of Hordeum vulgare. Older, vegetative tissues catabolised (R,S,)-ABA more efficiently than their younger counterparts. In contrast, small, immature seeds of Pisum sativum catabolised (R,S,)-ABA more effectively than larger, immature seeds of this species. Light did not appear to influence ABA biosynthesis but markedly enhanced ABA catabolism. Light stimulated the overall rate of ABA catabolism in both vegetative and non-vegetative tissue. Water stress reduced ABA catabolism in Hordeum vulgare leaves but had little effect on this process in Phaseolus vulgaris seedlings. Pretreatment of tissues with (R,S,)-ABA retarded the catabolism of (R,S,)-[2-Â¹â ´C]-ABA, negating ABA-induced conversion to PA. Cycloheximide inhibited ABA biosynthesis and catabolism but did not affect ABA conjugation. Chloramphenicol and lincomycin had little or no effect on ABA metabolism suggesting that the enzymes involved were labile and cytoplasmic in origin. Ancymidol and cycocel inhibited ABA biosynthesis while AM01618 stimulated this process. The cytokinins, benzyladenine, kinetin, isopentenyl adenine and zeatin also inhibited ABA biosynthesis. These results are discussed in relation to the possible involvement of carotenoids in ABA biosynthesis. AM01618, ancymidol andcycocel did not significantly influence the conversion of ABA to PA and DPA while cytokinins appeared to enhance this process only in vegetative tissue. The information derived from these studies was then used in attempts to develop a cell-free system from higher plants capable of metabolising ABA. A cell-free system prepared from imbibed Hordeum vulgare cv. Dyan embryos biosynthesized and catabolised ABA. This is the first demonstration of a cell-free system from non-vegetative tissue capable of metabolising ABA and could prove useful for elucidating its biosynthetic route. This cell-free system generated the terpenyl pyrophosphates IPP, FPP and GGPP from MVA. ABA was produced from both MVA and IPP in the presence of 0â‚‚ and NADPH. The biosynthesis of ABA was stimulated by the addition of the squalene 2,3-oxide cyclase and kaurene synthetase inhibitor, AM01618 and a "cold-pool trap" of (R,S,)-ABA. Ancymidol, cycocel and cytokinins reduced incorporation of label from MVA into ABA. Similar cell-free preparations, in the absence of AM01618, converted (R,S,)-[2-Â¹â ´-C]-ABA into PA, 7'-hydroxy ABA and water-soluble conjugates. Although the methyl ester of (R,S,)-ABA was efficiently hydrolysed in this cell-free system no DPA was generated. The possible involvement of mixed function oxidase activity and soluble oxidases is discussed in relation to ABA metabolism. While cell-free preparations from Persea americana cv. Fuerte mesocarp and immature seeds of Pisum sativum and Phaseolus vulgaris were unable to synthesize ABA from MVA, these tissue homogenates converted ABA into more polar acidic products. PA and DPA were identified as products of ABA catabolism in extracts from immature seeds of Phaseolus vulgaris and the l',4'-cis diol of ABA in extracts from Pisum sativum immature seeds
Keywords: Plants -- Metabolism; Plant cells and tissues; Abscisic acid -- Metabolism